(untitled) (Italian Journal of Public Health, 2011)
Background: Private health care providers are largely the first point of contact for Tuberculosis (TB) patients, who either undergo treatment from private practitioners or buy medicines on their own from private pharmacies. Aims: This study assessed the availability, sale and magnitude of anti-tuberculosis drugs dispensing through private pharmacies. Methodology: The present cross sectional study was conducted among private pharmacies located along the national highway from Thalassery to Payyannur in the Kannur district of Kerala, India. A total of 38 private pharmacies located along the national highway were included. Results: The duration that anti–TB drugs had been on sale showed that 74.3% of pharmacies had started to sell these drugs only less than ten years ago. The majority (82.9%) of the private pharmacies received up to 5 prescriptions for anti-TB drugs weekly. Out of the total of 35 pharmacies selling these drugs, 22 (62.9%) reported an increase in their sales. Nearly 82% of those pharmacies that reported an increase in the sale of anti-TB drugs were selling these drugs for less than the past ten years. Conclusions: The current study shows that a large number of tuberculosis patients are still approaching private pharmacies for anti-tuberculosis drugs. This tendency has to be completely stopped and needs properly planned strategies to encourage private pharmacies to participate actively in the DOTS (Direct Observation Treatment Short course) program of the Government, by providing them attractive alternative incentives.